Image Projection Over The Edge - Abu, Nur Azman; Siaw Lang, Wong; Shahrin, Sahib (2010)
Image projection is usually associated with image enlargement projected on screen or large display devices. The objective of this paper is to achieve sharper image projection and thinner transition over the edge. Tchebichef moment has been chosen here since it performs better than the popular Discrete Cosine Transform. This transform integrates a simplified mathematical framework technique using matrices, as well as a block-wise reconstruction technique. The result shows Tchebichef moment gives better image projection over the edge on graphical and real images.